Dynamics of attentional bias for food in Dutch and Chinese children and the role of executive control. (1st December 2019) - Liu, Yu; Nederkoorn, Chantal; Roefs, Anne
Abstract: The current study examined the relationships among dynamics of attentional bias for food, executive control and adjusted BMI% among children. 106 Dutch (8-12 years old, 56.60% female) and 99 Chinese children (9-13 years old, 44.44% female) participated in the study. All participants first completed a self-report hunger questionnaire, and then the food dot-probe task and attention network task were administered. Both mean attentional bias and the variability of attentional bias were computed as people often experience the opposite goals to approach and avoid palatable food. We hypothesized that only the variability of attentional bias for food would be positively related to adjusted BMI%. In addition, such association would be moderated by the executive control, which would be also negatively related to adjusted BMI%. The results showed that adjusted BMI% was only positively associated with the variability of attentional bias for food in Dutch children. However, such association did not exist in Chinese children and executive control was not a significant moderator of the relation between the variability of attentional bias for food and adjusted BMI% in both Dutch and Chinese children. Unexpected, compared with Dutch children, Chinese children had stronger executive control, which was directly related to a lower adjusted BMI%. This study emphasized both TL-BS variability for food and executive control might have an effect on adjusted BMI%, in addition, culture possibly serve as a reason for the inconsistent results between Dutch and Chinese children.